2020
DOI: 10.1037/xhp0000728
|View full text |Cite
|
Sign up to set email alerts
|

Overt attentional capture by reward-related stimuli overcomes inhibitory suppression.

Abstract: Salient-but-irrelevant distractors can automatically capture attention and eye-gaze in visual search. However, recent findings have suggested that attention to salient-but-irrelevant stimuli can be suppressed when observers use a specific target template to guide their search (i.e., feature search). A separate line of research has indicated that attentional selection is influenced by factors other than the physical salience of a stimulus and the observer's goals.For instance, pairing a stimulus with reward has… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 63 publications
(157 reference statements)
4
21
0
1
Order By: Relevance
“…In this case, the independent effects of value and location indicate that a fixed, limited amount of suppression was applied to this frequent location, and this suppression applied equally to both types of distractor. Consequently, high-value distractors were more likely to 'break through' this suppression and capture attention, thus LOCATION-BASED SUPPRESSION AND REWARD LEARNING 28 slowing search -an idea that is consistent with conclusions from previous research that has examined effects of reward in the context of other forms of inhibition (Pearson et al, 2020;Wang et al, 2014).…”
Section: Location-based Suppression and Reward Learning 27supporting
confidence: 77%
See 2 more Smart Citations
“…In this case, the independent effects of value and location indicate that a fixed, limited amount of suppression was applied to this frequent location, and this suppression applied equally to both types of distractor. Consequently, high-value distractors were more likely to 'break through' this suppression and capture attention, thus LOCATION-BASED SUPPRESSION AND REWARD LEARNING 28 slowing search -an idea that is consistent with conclusions from previous research that has examined effects of reward in the context of other forms of inhibition (Pearson et al, 2020;Wang et al, 2014).…”
Section: Location-based Suppression and Reward Learning 27supporting
confidence: 77%
“…Previous studies have found medium to very large effect sizes (d z = 0.54-2.20) for the influence of reward on attention in tasks similar to that used here (e.g., Le Pelley et al, 2015;Pearson et al, 2015Pearson et al, , 2016Watson et al, 2019aWatson et al, , 2019bWatson et al, , 2020, and large effect sizes (d z = 0.69-2.15) for the influence of statistical learning about distractor location (Failing, Feldmann-Wüstefeld, et al, 2019;Failing & Theeuwes, 2020;).…”
Section: Participants and Apparatussupporting
confidence: 64%
See 1 more Smart Citation
“…Even though looking at the high-reward-signalling distractor was counterproductive (as it triggered the omission of a relatively large reward), participants came to look at it more often than the low-reward-signalling distractor, thereby cancelling more high rewards. Subsequent research has indicated that this overt attentional bias to signals of reward is largely immune to top-down control, in that it persists when participants are explicitly instructed that looking at the reward-signalling distractor will result in reward omission (Kim & Anderson, 2019;Pearson, Donkin, Tran, Most, & Le Pelley, 2015), and under search conditions that allow physically salient distractors to be suppressed (Pearson, Watson, Cheng, & Le Pelley, 2020). However, the magnitude of VMAC has been shown to increase when cognitive control resources are depleted (Watson, Pearson, Chow, et al, 2019), which suggests a limited role for top-down control processes in reducing (but not preventing) the likelihood of capture by signals of reward.…”
Section: Introductionmentioning
confidence: 99%
“…There are various pathways through which reward might be expected to influence performance in this procedure. Notably, evidence suggests that reward-signaling stimuli are more likely (than non-reward stimuli) to capture and hold attention (Anderson, 2016;Failing & Theeuwes, 2018;Le Pelley et al, 2016;Watson, Pearson, Theeuwes, Most & Le Pelley, 2020) and are particularly difficult to suppress via inhibitory processes (e.g., Pearson, Watson, Cheng & Le Pelley, 2020;Wang, Duan, Theeuwes & Zhou, 2014). Hence, we hypothesized that participants may have difficulty disengaging attention from reward-signaling stimuli in the preview display, which would enhance performance when the target subsequently appeared at one of these previewed THE EFFECT OF REWARD ON PREVIEW BENEFIT locations (i.e., old-target-location trials) and impair performance when the target appeared at a new location.…”
Section: Reward Does Not Modulate the Preview Benefit In Visual Searchmentioning
confidence: 99%